High-Power Excitation of Spintronic THz Emitter in the Back-Cooled Reflection Geometry - Vogel, Tim; Omar, Alan; Mansourzadeh, Samira; Wulf, Frank; Sabanés, Natalia Martín; Müller, Melanie; Seifert, Tom; Weigel, Alexander; Jakob, Gerhard; Kläui, Mathias; Pupeza, Ioachim; Kampfrath, Tobias; et al. (2022 Conference on Lasers and Electro-Optics, CLEO 2022 - Proceedings, 2022)
We present THz generation in a back-cooled spintronic THz emitter in reflection geometry, excited with a high-average power Yb-laser providing up to 18.5 W at 400 kHz repetition rate. This allows us to increase the THz power.
CRIS-Team Scopus Importer:2023-03-27